OBJEK EVALUASI PENDIDIKAN - Suddin Bani (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
Evaluation is a tool, which is used to measure the success level of a program. In measuring something, it must use appropriate tool based on the existing indicators. Evaluation in education is related to activity or process of education that becomes center of attention. The object of study is cognitive (knowledge and understanding), affective (attitudes and ideas), and psychomotoric (skills and habits), the determination of the instrument is associated with aspects that will be be assessed.